2015
DOI: 10.4103/0019-509x.175838
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status at presentation, comparison of assessment tools, and importance of arm anthropometry in children with cancer in India

Abstract: The prevalence of malnutrition in Indian children with cancer at presentation is very high ranging from 40% and 80% depending on the method used for assessment, being higher with MUAC and lowest with BMI. Either MUAC alone or TSFT + MUAC (wherever feasible) should be used for screening for malnutrition in children with cancer at diagnosis to plan timely nutritional interventions, reduce the treatment-related morbidity and optimise their chance of long-term cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 1 publication
3
14
0
Order By: Relevance
“…1,16 Some studies have also revealed strong correlations between triceps skinfold thickness and FM determined by BIA or D 2 O; [26][27][28] the same occurring with FFM determined by mid-arm muscle mass circumference and triceps skinfold thickness. 17,29 Other studies with children and adolescents with cancer show that FM can be predicted with reasonable confidence using arm anthropometry. They demonstrated a good correlation between MUAC and DXA.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1,16 Some studies have also revealed strong correlations between triceps skinfold thickness and FM determined by BIA or D 2 O; [26][27][28] the same occurring with FFM determined by mid-arm muscle mass circumference and triceps skinfold thickness. 17,29 Other studies with children and adolescents with cancer show that FM can be predicted with reasonable confidence using arm anthropometry. They demonstrated a good correlation between MUAC and DXA.…”
Section: Discussionmentioning
confidence: 94%
“…Many different techniques are available, from relatively easy-to-use, cheap methods, including weight, height, BMI, circumferences, and skinfold measurement, to more expensive and technical approaches, such as BIA, D 2 O, dual-energy X-ray absorptiometry (DXA), and others. 15 , 16 , 17 , 18 Each of these methods has advantages and limitations. The current study aimed to determine the association between different body composition measures (anthropometry, BIA, and D 2 O dilution) to find a useful, quick, and easy instrument for daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus of Brazilian oncological nutrition specialists describes TSF as one of the variables for nutritional diagnosis to be used before, during and after chemotherapy and radiotherapy in children over the age of 2 years [31]. Measuring body fat using the tricipital skinfold enables measuring both the quantity and the body distribution of adipose tissue, thus meaning a better correlation with the excess weight than BMI [25,32]. In the sample studied we found 24.0% excess fat with this measure.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a statistically significant difference in relation to height for age between M1 and M3 (p=0.016); and between M2 and M3 (p=0.006), demonstrating a possible deficit in growth over treatment. It is known that reduction in linear growth is a common finding in cancer survivors, although most of the survivors treated with chemotherapy reach normal height and puberty when adults [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation